Interprofessional education and practice guide: designing ethics-orientated interprofessional education for health and social care students. Issue 6 (2nd November 2019) - Machin, L.L.; Bellis, K. M.; Dixon, C.; Morgan, H.; Pye, J.; Spencer, P.; Williams, R.A.
ABSTRACT: Health and social care professionals are required to work together to deliver person-centered care. Professionals therefore find themselves making decisions within multidisciplinary teams. For educators, there has been a call to bring students from differing professions together to learn to enable more effective teamwork, interprofessional communication, and collaborative practice. This multidisciplinary working is complicated by the increasingly complex nature of ethical dilemmas that health and social care professionals face. It is therefore widely recognized that the teaching and learning of ethics within health and social care courses is valuable. In this paper, we briefly make the case in support of teaching and learning health and social care ethics through the medium of interprofessional education (IPE). The purpose of this paper is to provide guidance to educators intending to design ethics-orientated IPE for health and social care students. The guidance is based on the ongoing experiences of designing and implementing ethics-orientated IPE across five departments within two universities located in the North of England over a five-year period. Descriptions of the ethics-orientated IPE activities are included in the guide, along with key resources recommended.